Hepatoprotective Activity of Superliv Liquid and Repchol in CCl4 Induced FLKS Syndrome in Broilers - Sonkusale, P.; Bhandarker, A.G.; Kurkare, N.V.; Ravikanth, K.; Maini , S.; Sood, D. (International Journal of Poultry Science, 2010)
A 6 week long experimental trial was conducted to study whether the supplementation of herbal products Superliv liq. and Repchol (supplied by M/S Ayurvet Limited, Baddi, India) are efficacious in treatment of liver and kidney due to CCl4. A total of 75 Cobb day old broilers were divided into three equal groups (n = 25). Group A served as negative control, group B (positive control) and C (treatment group) were induced with FLKS with CCL4 @1 ml/kg body weight orally, administered every 3rd day during 15-28 days of trial. Treated group C were given Superliv Liq. @5 ml/100 chicks/day for first 2 weeks and @ 10 ml/100 chicks/day for 3-6 weeks along with drinking water in combination with Repchol@500 gm/ton of feed from 0-6 weeks. Fatty liver and kidney syndrome lead to depression in growth rate, lowered feed efficiency and disturbances in immunopathological and biochemical parameters. Final mean body weight of group C was significantly (p<0.01) higher than group A and B. A significant (p<0.01) decrease in feed conversion ratio was observed in group C as compared to group B. A significant (p<0.01) decrease in level of cholesterol, triglycerides, HDL, VLDL, creatinine, liver enzymes (SGOT and SGPT) and increase in serum protein level was recorded in group C as compared to group B on 28th and 42nd day of experiment, which was in confirmation with the values of negative control group A, falling into normal range. Gross and histopathology of liver and kidney revealed that there was mild congestion and negligible degenerative changes in group C in contrast to severe changes of FLKS syndrome in group B. It can be concluded that liver tonic Superliv liquid along with phytoadditive Repchol (supplement for choline and biotin) efficaciously ameliorated the CCl4 induced toxicity, when administered prophylactically in broilers.